Health and physical activity in urban neighbourhoods. Case study: Shah Alam City, Selangor, Malaysia / Oliver Ling Hoon Leh ... [et al.] - Ling, Oliver Hoon Leh; Mohamed Musthafa, Siti Nur Afiqah; Hamzah, Muhammad Solahuddin; Marzukhi, Marlyana Azyyati; Mabahwi, Nurul Ashikin (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Environmental health is referring to the health of people in relation to environmental quality. Due to rapid urbanisation, more people are living in urban neighbourhoods. Urban planning and design aspects including the neighbourhood environment are potentially affecting the human healthy lifestyle and health condition. Thus, the relationship between Malaysian neighbourhood environmental aspects and human health has become the concern of this research. One of the neighbourhood units in Shah Alam city had been chosen as the study area for this purpose. Questionnaire survey had been carried out to examine the health condition and physical activeness of residents. Besides, the perception of residents on the quality of neighbourhood environmental aspects also had been collected in the questionnaire survey. The health condition of residents was measured by non-communicable diseases (NCD) and the physical activeness was measured in duration as well as the frequency of physical exercise activities. The study found that the quality of neighbourhood environmental aspects significantly increased the physical activeness of respondents. The physical activeness was positively associated with human health as measured in NCD (heart diseases and high blood pressure, HBP). It shows that neighbourhood environmental (physical and social) aspects are potentially affecting the healthy life of people living in the neighbourhood.